THE CONSTRAINTS OF SMEs IN THE REPUBLIC OF MACEDONIA IN THE PROCESS OF PUBLIC E-PROCUREMENT - Janevski, Zoran; Davitkovska, Elena; Petkovski, Vladimir (Institute of Economics – Skopje, 2016)
The public procurement process can be recognized as one of the crucial processes in developing countries. The most vital issues that need to be addressed with public procurement are the competitiveness, transparency and, accountability. With the developing trends of the digital economy, the process of public procurement also has developed into more effcient electronic procurement process. This paper addresses the impact of obligatory public e-procurement on small and medium enterprises in Republic of Macedonia. The main goal of this research is to indicate the advantages and constraints of public e-procurement process for the SMEs in Republic of Macedonia through the presentation of case study that is part of the process itself.
Keywords: Public procurement; SMEs; electronic procurement; public e-procurement